Drivers of Employee Turnover: Workload, Job Satisfaction, and Organisational Commitment - Dyah Ayu Pitaloka; Ignatius Soni Kurniawan; Nala Tri Kusuma (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2026)
High turnover intention in the Business Process Outsourcing (BPO) industry, including at PT Infomedia Nusantara Yogyakarta, presents a critical challenge to organisational sustainability by raising recruitment costs, lowering productivity, and disrupting workforce stability. This study investigates the influence of workload, job satisfaction, and organisational commitment on employee turnover intention at PT Infomedia Nusantara Yogyakarta. A quantitative approach was employed using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) method with SmartPLS 4. Accidental sampling was applied to a sample of 100 employees, who completed structured questionnaires. Analysis involved assessing the outer model for validity and reliability, followed by inner model evaluation and hypothesis testing through bootstrapping. The findings indicate that workload has a positive and significant effect on turnover intention, while organisational commitment has a negative and significant effect. Job satisfaction showed a negative but insignificant influence. Collectively, these variables explain 49.2% of the variance in turnover intention (Adjusted R² = 0.492). These findings suggest that in a high-pressure, contract-based BPO environment, workload intensity and organisational commitment play a more decisive role in shaping employees’ intention to leave than job satisfaction. Accordingly, workload management and organisational commitment emerge as primary retention strategies in service-intensive BPO organisations.